Nucleotide sequence of the repressor gene of the RA1 tetracycline resistance determinant: structural and functional comparison with three related Tet repressor genes. - Unger, B (1984)
The tetracycline resistance determinant of RA1 was cloned. It consists of at least two genes oriented with opposite polarity, tetA for resistance and tetR for regulation. The transcriptional control sequence was identified and analyzed. It consists of overlapping promotors with divergent orientation and a tandem arrangement of operators. Nucleotide sequencing revealed two open reading frames. One codes for a protein which was identified as a Tet repressor by comparing its primary structure with those of other Tet repressors. The RA1 tetR gene codes for 218 amino acids with a calculated molecular weight of 24.4 kDa. In the primary sequence of the RA1-, pSC101-, Tn10-, and RP1/Tn1721-encoded Tet repressors, 36% of the amino acids are identical. This homology is clustered within the first 150 amino acids, 49% of which are identical among all four proteins. These results are discussed with respect to their structure and function in comparison to other DNA binding proteins.